Compare and contrast the extent of content compliance in public performance audit reports published in South Africa and Australia - Gomez, Samantha Esmeralda (My University, 2015)
Public performance auditing is a type of auditing government departments’ use to review three specific aspects (efficiency, effectiveness and economy) of a sector, department or project. Upon completion of a public performance audit, the relevant supreme audit institution releases a performance audit report. The purpose of this study is to determine the level content compliance in these public performance audit reports with the international performance audit standards ISSAI 3000-3001. This study compares the level of content compliance in South Africa, a developing countries against Australia, a developed country. A type of text analysis was used to collate the levels of content compliance in a total of fifty reports, twenty-five reports published by the Auditor General of South Africa (AGSA) and twenty-five reports published by the Australian National Audit Office (ANAO), during the period 2006 – 2013. The finding revealed that public performance audit reports published in Australia have a greater level of content compliance than reports published in South Africa. The results of the report further detail the content shortcomings in the reports reviewed. This study will assist both the AGSA and ANAO in highlighting content concerns in these performance audit report, which is the first step towards improvement.
Keywords: Public performance audit report; Auditor General of South Africa (AGSA); Australian National Audit Office (ANAO)